Paradoxes of gender - Lorber, Judith (New Haven : Yale University Press, 1994)
Annotation In this innovative book, a well-known feminist and sociologist challenges our most basic assumptions about gender. Judith Lorber argues that gender is wholly a product of socialization, subject to human agency, organization, and interpretation, and that it is a social institution comparable to the economy, the family, and necessity of gender, she envisions a society structured for equality, where no gender, racial, ethnic, or social class group is allowed to monopolize positions of power.
pt. 1. Producing gender. "Night to his day": the social construction of gender ; Believing is seeing: biology as ideology ; How many opposites? Gendered sexuality ; Men as women and women as men: disrupting gender ; Waiting for the goddess: cultural images of gender. -- pt. 2. Gender in practice. Out of Eden: the social evolution of gender ; Rocking the cradle: gender and domestic labor ; Daily bread: gender and domestic labor ; Separate and not equal: the gendered division of paid work. -- pt. 3. The politics of gender. Guarding the gates: the micropolitics of gender ; The visible hand: gender and the state ; Dismantling Noah's ark: gender and equality.
Includes bibliographical references (pages 335-411) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Sex role; Gender identity; Social institutions; Feminist theory; Gender identity; Social institutions; Gender Identity; Gender Role; Feminist theory; Rôle selon le sexe; Identité de genre; Institutions sociales; Théorie féministe.; sex role; social institutions; SOCIAL SCIENCE -- Gender Studies; HISTORY -- General; Feminist theory; Gender identity; Sex role; Social institutions; Sekseverschillen; Theorieën.; Relações de gênero (desenvolvimento social;aspectos culturais); Interação interpessoal; Sex role; Feminist theory; Gender identity; Rôle selon le sexe; Identité sexuelle; Institutions sociales; Feminism